Penerapan Moderasi Beragama Di Masyarakat Desa Baru Kecamatan Batang Kuis - Muhammad Zuhri; Annisa Firdaus; Chandrini Faiza Ananda; Rajin Sitepu (Universitas Cokroaminoto Yogyakarta, 2021)
Religion plays an important role in social life to regulate human life and direct it to goodness in the world. This study aims to gain anunderstanding and description of religious moderation and religious harmony in the Baru Village. The research method used in this research is the field observation research method and also direct interviews through the Public Discussion forum in the Desa Baru and also the Webinar Seminar organized by the KKN 127 Group Deli Serdang Regency. The results of research tthat have known that religious moderation in the Desa Baru area is still very low. This can be seen from the people who still do not understand the concept of religious moderation itself and the local community still lives by following the dynamics of the flow of life as in general. When viewed from the harmony between religious communities, the people of Desa Baru highly uphold the harmony where mutual respect and respect for differences. Moreover, the community in the area can be said to be plural because it consists of various ethnic groups, cultures, and religions. There are Javanese, Malay, and Batak tribes who occupy the area of the Desa Baru.